Program Pengembangan Soft Skill Melalui Pelatihan Public Speaking untuk Siswa SMK Attaufiqiyyah di Kecamatan Baros Kabupaten Serang - Mita Mita; TB Nurwahyu; Amelia Febriyanti; Syifa Hyatin Nufus; Muslihatun Amaliah; Ripahiyah Ripahiyah (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2025)
Soft skill development is a crucial aspect in preparing students to face the challenges of the world of work and further education. One of the skills that needs to be improved is public speaking, which is the ability to speak in public effectively, confidently, and in a structured manner. This community service activity was carried out at SMK Attaufiqiyyah, Baros District, Serang Regency, with the aim of improving students' public speaking skills through intensive training and hands-on practice. The implementation method includes the delivery of basic public speaking materials, interactive question and answer sessions, and practice simulations to become Master of Ceremony (MC) in various event contexts. This approach is designed to build confidence, train the structure of the delivery of ideas, and hone students' verbal communication skills. The results of the activity showed a significant increase in the aspects of confidence, speaking ability, and activeness of students in interacting. Students also show better ability to overcome nervousness when appearing in public and conveying ideas clearly and systematically. This program makes a positive contribution to the development of soft skills of vocational school students, as well as being an important provision in shaping the communicative and professional character needed in the world of work and social life. The sustainability of similar programs is highly recommended to strengthen the readiness of the younger generation to face future challenges.